Isochrone Fitting of Galactic Globular Clusters—Ⅵ.High-latitude Clusters NGC 5024(M53),NGC 5053,NGC 5272(M3),NGC 5466,and NGC 7099(M30) - G.A.Gontcharov; S.S.Savchenko; A.A.Marchuk; C.J.Bonatto; O.S.Ryutina; M.Yu.Khovritchev; V.B.Il'in; A.V.Mosenkov; D.M.Poliakov; A.A.Smirnov (天文和天体物理学研究, 2024)
We fit various color-magnitude diagrams(CMDs)of the high-latitude Galactic globular clusters NGC 5024(M53),NGC 5053,NGC 5272(M3),NGC 5466,and NGC 7099(M30)by isochrones from the Dartmouth Stellar Evolution Database and Bag of Stellar Tracks and Isochrones for α-enrichment[α/Fe]=+0.4.For the CMDs,we use data sets from Hubble Space Telescope,Gaia,and other sources utilizing,at least,25 photometric filters for each cluster.We obtain the following characteristics with their statistical uncertainties for NGC 5024,NGC 5053,NGC 5272,NGC 5466,and NGC 7099,respectively:metallicities[Fe/H]=-1.93±0.02,-2.08±0.03,-1.60±0.02,-1.95±0.02,and-2.07±0.04 dex with their systematic uncertainty 0.1 dex;ages 13.00±0.11,12.70±0.11,11.63±0.07,12.15±0.11,and 12.80±0.17 Gyr with their systematic uncertainty 0.8 Gyr;distances(systematic uncertainty added)18.22±0.06±0.60,16.99±0.06±0.56,10.08±0.04±0.33,15.59±0.03±0.51,and 8.29±0.03±0.27 kpc;reddenings E(B-V)=0.023±0.004,0.017±0.004,0.023±0.004,0.023±0.003,and 0.045±0.002 mag with their systematic uncertainty 0.01 mag;extinctions Av=0.08±0.01,0.06±0.01,0.08±0.01,0.08±0.01,and 0.16±0.01 mag with their systematic uncertainty 0.03 mag,which suggest the total Galactic extinction Av=0.08 across the whole Galactic dust to extragalactic objects at the North Galactic Pole.The horizontal branch morphology difference of these clusters is explained by their different metallicity,age,mass-loss efficiency,and loss of low-mass members in the evolution of the core-collapse cluster NGC 7099 and loose clusters NGC 5053 and NGC 5466.